Experimental Evaluation of Load Distribution between Piles in Case of Block Failure - Aksoy, Huseyin Suha; Ozpolat, Aykut (Mdpi, 2023)
In this study, the load distribution of the piles in the pile group was investigated in the case of the pile raft foundations failure under the effect of vertical loads in cohesive soils. For this purpose, loading tests were carried out on model pile groups in the laboratory. In addition, the effects of these conditions on the load distribution between the piles were examined by changing the pile spacing and soil properties. As a result of the experiments, it was determined that the piles in the corner region carried more load than the ones in the center region in small settlement amounts as in the literature. However, it has been determined that as the amount of settlement in the pile foundation increases, the soil between piles behaves like a block and approaches failure, and the piles in the center region of the pile group carry more load. As a result of excessive settlement, a fracture surface formed around the block and therefore the corner piles of the block began to carry less load. It has been determined that failure analyses should be performed considering the load carried by the corner piles after failure due to excessive settlement.
Keywords: pile group; clayey soil; model tests; pile load distribution; consolidation pressure